2010
DOI: 10.2478/v10085-010-0011-x
|View full text |Cite
|
Sign up to set email alerts
|

Metals removal during estuarine mixing of Arvand River water with the Persian Gulf water

Abstract: Abstract:In the present study, the removal of dissolved and colloidal Cd, Co, Cu, Ni and Zn in Arvand River water during estuarine mixing with the Persian Gulf water is investigated. The flocculation process was investigated for a series of mixtures with salinities ranging from 0.48 to 30.3‰. The flocculation rates were indicative of the non-conservative behavior of studied metals during estuarine mixing. Rapid flocculation in the low salinity regimes was observed. The order of the final flocculation rate of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Plant growth is inhibited by chromium toxicity [68] [95]. This work showed that the seeds failed to germinate by chromium treatment except at 0.2 mM chromium concentration.…”
Section: Effect Of Chromium On Proteinmentioning
confidence: 99%
“…Plant growth is inhibited by chromium toxicity [68] [95]. This work showed that the seeds failed to germinate by chromium treatment except at 0.2 mM chromium concentration.…”
Section: Effect Of Chromium On Proteinmentioning
confidence: 99%
“…In bottom fishes and carb species caught at Shatt Al-Arab river, certain heavy metals were bio monitored (Rahmanpour et al, 2014), and certain levels of chemical elements were recorded in the water of Shatt Al-Arab river (Abdulreza et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the sediments at the bottom of the water body can play a major role by their ability to accumulate the elements and different types of pollutants, so they can be a source of these elements specially when physicochemical factors changed which help in the release of these elements to the overlying water column (Hassan et al, 2008). Factors like temperature, velocity of water, pH, Eh ionic strength, fine sediment particles, increases the release of heavy metals to the water environment particularly when the surface of sediment is filled with heavy metals and the concentration of them less in the overlying water column (Davis et al, 1991;Karbassi et al, 2005;Al-Atbee, 2018;Hassan, 2018). The aim of this present study is focused on the estimation of some heavy metals in an important regional water of Iraq which considered as marine navigation road (trading and export oil) between Iraq and Iran, and between Iraq and Kuwait.…”
Section: Introductionmentioning
confidence: 99%